Quasar Sightline and Galaxy Evolution (QSAGE) survey – II. Galaxy overdensities around UV luminous quasars at z = 1–2. Issue 3 (17th July 2020) - Stott, J P; Bielby, R M; Cullen, F; Burchett, J N; Tejos, N; Fumagalli, M; Crain, R A; Morris, S L; Amos, N; Bower, R G; Prochaska, J X
ABSTRACT: We demonstrate that the UV brightest quasars at z = 1–2 live in overdense environments. This is based on an analysis of deep Hubble Space Telescope WFC3 G141 grism spectroscopy of the galaxies along the lines-of-sight to UV luminous quasars in the redshift range z = 1–2. This constitutes some of the deepest grism spectroscopy performed by WFC3, with four roll angles spread over a year of observations to mitigate the effect of overlapping spectra. Of the 12 quasar fields studied, 8 display evidence for a galaxy overdensity at the redshift of the quasar. One of the overdensities, PG0117 + 213 at z = 1.50, has potentially 36 spectroscopically confirmed members, consisting of 19 with secure redshifts and 17 with single-line redshifts, within a cylinder of radius ∼700 kpc. Its halo mass is estimated to be log ( M /M⊙ ) = 14.7. This demonstrates that spectroscopic and narrow-band observations around distant UV bright quasars may be an excellent route for discovering protoclusters. Our findings agree with previous hints from statistical observations of the quasar population and theoretical works, as feedback regulated black hole growth predicts a correlation between quasar luminosity and halo mass. We also present the high signal-to-noise rest-frame optical spectral and photometric properties of the quasars themselves.